If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -1x = 2x + 7 Reorder the terms: 7 + -1x = 7 + 2x Add '-7' to each side of the equation. 7 + -7 + -1x = 7 + -7 + 2x Combine like terms: 7 + -7 = 0 0 + -1x = 7 + -7 + 2x -1x = 7 + -7 + 2x Combine like terms: 7 + -7 = 0 -1x = 0 + 2x -1x = 2x Solving -1x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1x + -2x = 2x + -2x Combine like terms: -1x + -2x = -3x -3x = 2x + -2x Combine like terms: 2x + -2x = 0 -3x = 0 Divide each side by '-3'. x = 0 Simplifying x = 0
| 7-x=2x-7 | | 2y^3-4y^2-5= | | 0.08(50)+0.40x=0.20(50+x) | | 9-4x=2x(3)+6 | | -3x+2=2 | | 10x-5=95 | | 2y^3-(4y^2)-5= | | 9-4x=2(3)+6 | | 4x-9x=5.5 | | 3x+6=4x+5 | | 3x+9=4x+3 | | 10-4d=-6 | | -9x^2-5x+1=0 | | 7+4(a-3)=14-(a+4) | | 2=12s-2 | | x-3-1=x-10 | | 23-6z=-25 | | 6x-2(3x+3)=6-4(9-5x) | | 4x-4.4+x-4= | | 6y^2=-5y+14 | | -3(4z-7)=3(6-2z) | | 4x+9=-103-10x | | 1.3+0.5x=0.8x-4.7 | | 6y^2=-5+14 | | 28-2x=6x+12 | | 12-k=3(k+8) | | -2w-5+9w=-23.2 | | 2l+2w=p | | 1x*1x+15x+36x=0 | | -6w+12+w=2-3w | | 4m+2=-2 | | 5x-18=-8 |